2013
DOI: 10.1603/me12280
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering Biology of <I>Culex</I> (Diptera: Culicidae) Mosquitoes in the Sacramento Valley of California

Abstract: At temperate latitudes, Culex (Diptera: Culicidae) mosquitoes typically overwinter as adult females in reproductive arrest and also may serve as reservoir hosts for arboviruses when cold temperatures arrest viral replication. To evaluate their role in the persistence of West Nile virus (WNV) in the Sacramento Valley of California, the induction and termination of diapause were investigated for members of the Culex pipiens (L.) complex, Culex tarsalis Coquillett, and Culex stigmatosoma Dyar under field, seminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 49 publications
4
79
0
2
Order By: Relevance
“…Winter infections were unlikely to have arisen by recent bites from infected mosquitoes, because Culex mosquito activity was very low in winter and all mosquitoes collected during winter months tested negative for WNV. Similar mosquito results were reported recently for other sites within the Davis and Sacramento areas (Nelms et al 2013b). In contrast, consistent opportunities existed for fecal-oral transfer at the overwintering roost.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Winter infections were unlikely to have arisen by recent bites from infected mosquitoes, because Culex mosquito activity was very low in winter and all mosquitoes collected during winter months tested negative for WNV. Similar mosquito results were reported recently for other sites within the Davis and Sacramento areas (Nelms et al 2013b). In contrast, consistent opportunities existed for fecal-oral transfer at the overwintering roost.…”
Section: Discussionsupporting
confidence: 91%
“…In temperate climates, winter temperatures are generally low, which, in conjunction with declining photoperiod, typically leads to Culex diapause or quiescence (Nelms et al 2013b). We captured some Culex host-seeking during the winter, and therefore it is possible that mosquitoes may have contributed to WNV transmission to crows at the winter roost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Autogenous populations of Cx. pipiens recently were detected in catch basins and manholes in the Sacramento Valley of California, 44 Marin County, 45 and Santa Clara County, 42 supporting the unpublished studies of Iltis (Iltis WG, unpublished dissertation) who reported widespread autogeny among pipiens populations throughout much of central California.…”
Section: Introductionsupporting
confidence: 58%
“…Thus, for these mosquitoes to become infected with WNV they require infection by VT, not oral infection, prior to overwintering. VT of WNV by Culex mosquitoes and subsequent detection in overwintering populations has been recorded [111,128]. Therefore, when considering RVFV in temperate regions outside Africa, it may be necessary to consider a similar overwintering model.…”
Section: Temperaturementioning
confidence: 99%